Perancangan Strategi Manajemen Risiko untuk Peningkatan Mutu Layanan Usaha Steam Motor dan Mobil Berdasarkan ISO 31000:2018: Cuci Steam “MY Wash” - Fajar; Ari Assrishan Sosh Mantoro; Dea Wisnu Ramdani; Fiqi Ardi Abdurahman Masdar; Alfiana (Indo Publishing, 2025)
This study aims to analyze and design a risk management strategy for My Wash Steam Motor and Mobil Salju by using the ISO 31000:2018 framework. The research employs a descriptive qualitative approach through observation, interviews, and document review to identify risks that affect service quality. Based on the findings, a total of 31 risks were identified, consisting of operational, customer-related, human resource, environmental, financial, competitive, and regulatory risks. These risks were analyzed using likelihood and impact assessments, arranged in a risk-level matrix to determine handling priorities, and accompanied by mitigation strategies relevant to the business conditions. The results indicate that several risks fall into the high–priority category, including vehicle damage, service quality complaints, long queues, unstable daily revenue, and competitive pressure from similar businesses. The proposed mitigation strategies include developing standard operating procedures (SOP), employee training, improving queue management, enhancing service quality, strengthening financial recording, implementing simple waste management, and increasing business differentiation. Overall, implementing risk management based on ISO 31000:2018 supports My Wash in improving service quality, minimizing potential losses, and strengthening business competitiveness..